Pengaruh Tingkat Pendapatan Masyarakat Terhadap Kewajiban Membayar Pajak Bumi dan Bangunan di Desa Wanio Timoreng Kecamatan Panca Lautang Kabupaten Sidenreng Rappang - Harlina Harlina (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
Abstract This research was conducted in Wanio Timoreng village, its purpose was to determine the Community Income Level against Paying Liabilities of Land and Building Tax at Wanio Timoreng Village of Panca Lautang District in Sidenreng Rappang Regency, and all factors that influence it. Data collection methods used were observation, literature study, questionnaire, and interview. Population was fifty-nine (59) people, all of them were accounted as sample. The results are the effect of income levels against the obligation to pay Land and Building Tax in Wanio Timoreng Village which resulting a good rate at 94,92%. The income level was in the medium category at 84,75%. The economic level was also in the medium category at 88,14%. The awareness to pay Land and Building Tax against income and economic level was good at 96,61%. Tax payment procedure was easy at 84,75%. People’s understanding of the obligation to pay the tax was good at 96,61%. The timeliness in paying the tax was on time at 72,88%. The tax designation for the development was good at 89,83%. Tax functions as the government’s financial resource were good at 84,75%. The increase in village’s infrastructural development throughout the results and management of land and building tax was up at 81,36%. The affecting factors such if there were people reluctant or tardy to pay Land and Building Tax was resistant at 89,83%. If the tax system is still difficult to be understood by the public without a good control by the government, it will inhibit at 52,54%.